The effectiveness of the dispute resolution mechanism of the World Trade Organization - Talgatova, K.S.; Baimagambetova, Z.M. (Bulletin of the Karaganda University “Law Series”, 2021)
At the present stage of Kazakhstan's participation in the World Trade Organization, the question of the effectiveness of the World Trade Organization dispute settlement body, as well as the interest of Kazakhstan in the further development of this mechanism becomes highly relevant. The research goal is a comprehensive review of the effectiveness of the dispute resolution body in the context of such criteria as timeframe, results of consideration of disputes, participation of countries in the World Trade Organization. In order to achieve this goal, the authors have identified the following areas of this study: analysis of the stages of dispute resolution by the dispute settlement body of the World Trade Organization, the study of the main arguments for the effectiveness of the dispute settlement body, the definition and disclosure of indicators affecting the effectiveness of the mechanism. The general scientific, private-scientific and other methods of research: historical, formal-logical, comparative-legal analyses and formal-legal method have been used. The normative-legal base consists of the norms of international law, published and unpublished materials of domestic and international legal practice, the author's empirical research in the field of national and international trade law. The authors analyzed Kazakhstan's development perspective as a participant of the World Trade Organization, including interaction with the dispute resolution body.